For the equation $3{x^2} + px + 3 = 0;(p > 0),$ if one of the roots is square of the other. Then P is equal to:
A $\dfrac{1}{3}$
B 1
C 3
D $\dfrac{2}{3}$
Answer
Verified
511.5k+ views
Hint: If h, k are roots of the quadratic equation $a{x^2} + bx + c = 0$ then $h + k = - \dfrac{b}{a},hk = \dfrac{c}{a}$ .
The given quadratic equation is $3{x^2} + px + 3 = 0$ . Let $\alpha $ and $\beta $ be the two roots of the above equation. Given that $\beta = {\alpha ^2}$ . We know if the quadratic equation is in the form $a{x^2} + bx + c = 0$ and $h,k$ are its roots then $h + k = - \dfrac{b}{a},hk = \dfrac{c}{a}$ . According to our question,$
\alpha + \beta = \alpha + {\alpha ^2} = - \dfrac{p}{3}{\text{ - - - - - - - - }}(1) \\
\alpha \beta = \alpha .{\alpha ^2} = {\alpha ^3} = \dfrac{3}{3} = 1{\text{ - - - - - - - }}(2) \\
$
From equation (2), ${\alpha ^3} = 1$ then cube roots of unity are $1,\omega ,{\omega ^2}$ . Since, p is positive, 1 can’t be the root of the given equation. On substituting $\omega $ in place of $x$ in equation (1).
$
\omega + {\omega ^2} = - \dfrac{p}{3}{\text{ }}[\omega = \dfrac{{ - 1 + \sqrt {3i} }}{2}] \\
\Rightarrow - 1 = - \dfrac{p}{3} \\
\Rightarrow p = 3 \\
$
Hence, option C is correct.
Note: In this problem first we will find the sum and product of the roots then use cube roots of unity and its application to reach the required answer.
The given quadratic equation is $3{x^2} + px + 3 = 0$ . Let $\alpha $ and $\beta $ be the two roots of the above equation. Given that $\beta = {\alpha ^2}$ . We know if the quadratic equation is in the form $a{x^2} + bx + c = 0$ and $h,k$ are its roots then $h + k = - \dfrac{b}{a},hk = \dfrac{c}{a}$ . According to our question,$
\alpha + \beta = \alpha + {\alpha ^2} = - \dfrac{p}{3}{\text{ - - - - - - - - }}(1) \\
\alpha \beta = \alpha .{\alpha ^2} = {\alpha ^3} = \dfrac{3}{3} = 1{\text{ - - - - - - - }}(2) \\
$
From equation (2), ${\alpha ^3} = 1$ then cube roots of unity are $1,\omega ,{\omega ^2}$ . Since, p is positive, 1 can’t be the root of the given equation. On substituting $\omega $ in place of $x$ in equation (1).
$
\omega + {\omega ^2} = - \dfrac{p}{3}{\text{ }}[\omega = \dfrac{{ - 1 + \sqrt {3i} }}{2}] \\
\Rightarrow - 1 = - \dfrac{p}{3} \\
\Rightarrow p = 3 \\
$
Hence, option C is correct.
Note: In this problem first we will find the sum and product of the roots then use cube roots of unity and its application to reach the required answer.
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
Write an application to the principal requesting five class 10 english CBSE